Exploring early Acheulian technological decision-making: A controlled experimental approach to raw material selection for percussive artifacts in Melka Wakena, Ethiopia. - Eduardo Paixão; Tegenu Gossa; Walter Gneisinger; João Marreiros; Sören Tholen; Ivan Calandra; Erella Hovers (PLoS ONE)
The evolution of human behaviour is marked by key decision-making processes reflected in technological variability in the early archaeological record. As part of the technological system, differences in raw material quality directly affect the way that humans produce, design and use stone tools. The selection, procurement and use of various raw materials requires decision-making to evaluate multiple factors such as suitability to produce and design tools, but also the materials' efficiency and durability in performing a given task. Therefore, characterizing the physical properties of various lithic raw materials is crucial for exploring changes in human interactions with their natural environment through time and space and for understanding their technological behaviour. In this paper, we present the first step in an ongoing program designed to understand the decision-making criteria involved in the use of raw materials by the early Acheulian tool-makers at the Melka Wakena (MW) site-complex, located on the Ethiopian highlands. We present the results of the first experimental step, in which we identified and measured the engineering properties of raw materials in the lithic assemblages. These data serve as an objective, quantifiable baseline for natural experiments as well as archaeological inquiries into the technological decision-making processes of early Pleistocene hominins in Africa.